IMPLEMENTASI PENDEKATAN REDESIGN THINKING DALAM PEMBELAJARAN ILMU PENGETAHUAN SOSIAL BAGI MAHASISWA PGSD - Ahsan Sofyan; Cantika Putri Aulia; Irma Ramadani (Jurnal Pendidikan Dasar Borneo (Judikdas Borneo), 2025)
This study focuses on the application of the Redesign Thinking approach to help elementary school teacher education students develop critical, analytical, and creative thinking skills in understanding and teaching Social Sciences material to students. The informants in this study were students, Social Studies Lecturers, Head of the PGSD Department, FKIP UBT. Data collection techniques used were interviews, observations and documentation studies. The data analysis process was through data reduction, data presentation and drawing conclusions. The results of the study showed that the application of the Redesign Thinking approach in social studies learning for PGSD students, in addition to improving the quality of learning, also prepared students to become innovative and creative teachers, and developed critical, analytical thinking skills, prospective teachers as the main capital in teaching social studies to elementary school students. The application of the Redesign Thinking approach helps students to develop the ability to collaborate, communicate, and adapt in facing changes and challenges of the times. students will be invited to work together in teams, discuss, and share ideas to create the best solutions in the learning process.